About critical and behavioral competences in Statistics Education - Campos, Celso Ribeiro; Perin, Andréa Pavan (Universidade Estadual de Campinas, 2020)
Research in Statistics Education has advanced intensely with the planning of activities aimed at the development of three competences, literacy, reasoning, and statistical thinking, which allow more meaningful learning of the concepts of this science. The deepening of these researches allowed the identification of another competence also important for this universe, which is the critical competence. The aim of this paper is to deepen the reflection on critical competence, highlight its evolution in research developed in the field of Statistical Education, and to present a fourth competence, which we call behavioral competence. In our analysis, we have observed that critical competence develops itself on two streams, sociopolitical and epistemological. Finally, based on several practical examples observed inside and outside the classroom, we show how behavioral competence has been identified.